Kepuasan Penumpang Terhadap Kualitas Pelayanan Protokol Kesehatan yang Diterapkan Oleh Yogyakarta International Airport - Raizuli Mahadika Putra mahadika (Formosa Journal of Multidisciplinary Research, 2022)
This study aims to determine the effect of service quality on passenger satisfaction, Yogyakarta International Airport, the quality of service in question includes 5 dimensions (tangibles, reliability, responsiveness, assurance, empathy). This research uses quantitative methods. Data collection techniques by distributing statements (questionnaires) in the form of a Likert scale with a sample of 93 respondents. The sampling technique used was the purposive sampling technique. The results of the analysis show that there is a positive and significant influence on the satisfaction of air transportation service users partially, which is 19,901. The results showed that 81.3% of Yogyakarta International Airport's customer satisfaction was influenced by service quality (X) which consisted of five dimensions of tangible, reliability, responsiveness, assurance, and empathy. The remaining 18.7% is influenced by other variables not examined such as price, cost, efficiency and effectiveness.